SAT0475 Locus of control of pain in patients with knee osteoarthritis. (23rd January 2014) - Nuñez, M.; Nuñez, E.; Lozano, L.; Sastre, S.; Saulό, A.; Nicodemo, C.; Segur, J.M.; Suso, S.
Abstract : Background: Knee osteoarthritis (OA) is a degenerative joint disease in which pain and disability tend to increase in parallel with the disease duration. As in other chronic diseases, pain together with functional disability supposes not only a reduced quality of life but also the need for sufferers to adapt. The importance of the concept of locus of control, i.e. the belief in the possibility and/or ability to control symptoms and achieve and maintain a specific level of health, has been suggested in patients with chronic pain. Objectives: To examine the relationship between locus of control of pain, health-related quality of life (HRQL) and satisfaction with treatment in patients with knee OA. Methods: Cross sectional study. Sociodemographic and clinical variables were collected. Pain control was assessed using the Multidimensional Pain Locus of Control scale and generic and knee OA-specific HRQL measured using the SF-36 and WOMAC, respectively. Pain intensity was measured by a visual analogue scale (VAS). Satisfaction with OA-related treatment was determined. Groups were compared using the Student's t test for continuous and the Chi 2 test for categorical variables. Relationships between continuous variables were analyzed using Pearson's correlation coefficient. Results: 260 patients, mean age 69.8 (SD 8) years, 206 (79.2%) female, 76.9% with a low educational level, and 59.2% living with a partner, were included. All patients except one had at least one chronic condition (mean 5.3 [SD 3.3]), of which the most frequent were hypertension (59%), depression/anxiety (27%), poor circulation (27%), high cholesterol (20%), cardiovascular disease (19%), diabetes (18%). 73% were fairly or very satisfied with the treatment received. Patients with greater internal locus (L) of control had better SF-36 and WOMAC scores (p<0.001) except for the SF-36 emotional role dimension. Significant correlations were found between the internal L control subscale and the SF-36 physical function dimension (34%) and between the same subscale and pain intensity (VAS) (p<0.01). Patients with greater satisfaction with treatment also had higher scores on the internal L subscale compared with those with less satisfaction p=0.004 (mean score 67.5 [SD 15] vs 59.6 [SD 19], respectively). Conclusions: Patients with greater internal locus of control have better HRQL (SF-36 and WOMAC), less pain and greater satisfaction with treatment. The coherence found between the measures used suggests that this type of beliefs should be taken into account in the development of strategies for tackling chronic diseases. This study was funded by the Spanish Ministry of Health grant FIS PS09/01148 References: Lopez-Olivo MA, Landon GC, Siff SJ, Edelstein D, Pak C, Kallen MA, Stanley M, Zhang H, Robinson KC, Suarez-Almazor ME. Psychosocial determinants of outcomes in knee replacement. Ann Rheum Dis 2011;70(10):1775-81. Rofail D, Taylor F, Regnault A, Filonenko A. Treatment satisfaction instruments for different purposes during a product's lifecycle–keeping the end in mind. Patient. 2011;4(4):227–240. Disclosure of Interest: None Declared